Scrubbing-resistant inorganic coating emulsion composition and preparation method thereof

By combining modified nanosilica, silicone modified acrylate and polyisocyanate crosslinking agent, a highly crosslinked network structure is formed, which solves the shortcomings of existing water-based coatings in terms of scrubbing resistance, weather resistance, adhesion and mechanical properties, and achieves high-performance and environmentally friendly coating effects.

CN119684859AActive Publication Date: 2025-03-25FOSHAN ROSF TECH CO LTD

Patent Information

Application Number
CN202411856102.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

Existing water-based coatings have shortcomings in scrubbing resistance, weather resistance, adhesion and mechanical properties, which are difficult to meet the needs of high-performance applications.

Method used

Using a combination of modified nanosilicon dioxide, silicone modified acrylate and polyisocyanate crosslinking agent, a highly crosslinked network structure is formed through a high-pressure homogenizer treatment, combining aqueous epoxy resin and titanate coupling agent to optimize inorganic-organic interface compatibility.

Benefits of technology

The hardness and flexibility of the coating are balanced, which significantly improves scrubbing and weather resistance, while maintaining good adhesion and mechanical properties, and are environmentally friendly and cost-effective.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of acrylate emulsion, in particular to a scrubbing-resistant inorganic coating emulsion composition and a preparation method thereof.The scrubbing-resistant inorganic coating emulsion composition is prepared from, by weight, 10%-15% of modified nano-silica, 50%-60% of organosilicone modified acrylate emulsion, 5%-10% of waterborne epoxy resin, 2%-5% of polyisocyanate cross-linking agent and 3%-5% of organobentonite. 0.5-1% of a titanate coupling agent, 2-3% of a functional additive, and the balance deionized water; through ingenious cooperation of the modified nano silicon dioxide, the organic silicon modified acrylate and the polyisocyanate cross-linking agent, a highly cross-linked network structure is formed. According to the structure, the perfect balance of hardness and flexibility is realized, and meanwhile, the scrubbing resistance and the weather resistance are greatly improved; the introduction of the titanate coupling agent effectively improves the combination of an inorganic-organic interface, solves the problem of compatibility in a traditional hybrid system, and improves the overall performance and durability of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic ester emulsions, and in particular to a scrub-resistant inorganic coating emulsion composition and a preparation method thereof. Background Art

[0002] In recent years, with the improvement of environmental awareness and increasingly stringent regulations, water-based coatings have been increasingly widely used in the fields of construction, industry, and automobiles. However, traditional water-based coatings still have many deficiencies in terms of scrub resistance, weather resistance, adhesion, and mechanical properties, making it difficult to meet the needs of high-performance applications.

[0003] Current status of existing technologies:

[0004] 1. Application of nanomaterials: Researchers have tried to introduce inorganic nanomaterials such as nano-silicon dioxide and nano-zinc oxide into water-based coatings to improve the wear resistance and hardness of the coatings. However, the dispersion stability of nanoparticles and their compatibility with organic matrices remain a major challenge.

[0005] 2. Silicone modification: Silicone compounds are used to modify resins such as acrylates to improve the weather resistance and hydrophobicity of the coating. However, silicone modification often reduces the hardness and adhesion of the coating.

[0006] 3. Optimization of cross-linking system: Various cross-linking agents such as epoxy resins and isocyanates are introduced into water-based coatings to improve the chemical resistance and mechanical strength of the coating. However, the water dispersibility and reactivity of these cross-linking agents are often difficult to balance.

[0007] 4. Functional additives: Various functional additives such as coupling agents, leveling agents, etc. are used to improve the performance of coatings. However, the interaction between additives and their impact on overall performance have not been fully understood.

[0008] Problems with existing technologies:

[0009] 1. Performance contradiction: Increasing the hardness of the coating often sacrifices flexibility, and increasing hydrophobicity may reduce adhesion. These contradictions between properties are difficult to be effectively resolved in a single system.

[0010] 2. Poor dispersion stability: Nanoparticles tend to agglomerate in aqueous systems, resulting in uneven coating performance and poor long-term storage stability.

[0011] 3. Insufficient interfacial compatibility: The interfacial bonding between inorganic components (such as nanoparticles) and the organic matrix is ​​poor, which affects the overall performance and durability of the coating.

[0012] 4. Uneven cross-linking density: It is difficult to control the cross-linking reaction in the water-based system, which can easily lead to uneven cross-linking density and affect the overall performance of the coating.

[0013] 5. Insufficient weather resistance: Although silicone modification can improve weather resistance, it often affects other properties of the coating, such as hardness and adhesion.

[0014] 6. Conflict between environmental protection and performance: Reducing VOC content often leads to a decrease in coating performance, especially in terms of drying speed and film-forming properties.

[0015] 7. Multifunctionality is difficult to achieve: Existing technologies make it difficult to achieve high scrub resistance, excellent weather resistance, good adhesion and excellent mechanical properties in one formula.

[0016] 8. Balance between cost and performance: The introduction of high-performance components often significantly increases costs and limits the market application of products. Summary of the invention

[0017] In view of the above problems, it is of great practical significance and urgent need to develop a scrub-resistant inorganic coating emulsion composition and a preparation method thereof that can solve these technical problems at the same time.

[0018] The present invention discloses a scrub-resistant inorganic coating emulsion composition, comprising the following components in percentage by weight:

[0019] Modified nano-silicon dioxide 10-15%,

[0020] Silicone modified acrylic emulsion 50-60%,

[0021] Waterborne epoxy resin 5-10%,

[0022] Polyisocyanate crosslinker 2-5%,

[0023] Organic bentonite 3-5%,

[0024] Titanate coupling agent 0.5-1%,

[0025] Functional additives 2-3%,

[0026] Deionized water was added to 100%.

[0027] Specifically, the modified nano-silica is nano-silica modified by (3-glycidylpropoxy)trimethoxysilane (GPTMS).

[0028] Specifically, the organosilicon-modified acrylic ester emulsion is obtained by emulsion polymerization of acrylic ester monomers modified with 3-(trimethoxysilyl)propyl methacrylate (γ-MPS).

[0029] Specifically, the water-based epoxy resin is an aqueous dispersion of bisphenol A epoxy resin.

[0030] Specifically, the polyisocyanate crosslinking agent is water-dispersible hexamethylene diisocyanate trimer.

[0031] Specifically, the organic bentonite is bentonite modified by quaternary ammonium salt.

[0032] Specifically, the titanate coupling agent is isopropoxy tris(ethylenediamino-N-ethoxy) titanate.

[0033] The present invention also discloses a method for preparing the scrub-resistant inorganic coating emulsion composition, which comprises the following steps:

[0034] (1) mixing (3-glycidyl propoxy) trimethoxysilane and nano-silica in ethanol, reacting at 60-70° C. for 4-6 hours to obtain modified nano-silica;

[0035] (2) prepolymerizing 3-(trimethoxysilyl)propyl methacrylate with acrylic acid, butyl acrylate, and methyl methacrylate monomers, and then performing emulsion polymerization to obtain a silicone-modified acrylate emulsion;

[0036] (3) dispersing the modified nano-silica obtained in step (1) in deionized water and ultrasonically dispersing for 30 minutes;

[0037] (4) adding the organosilicon-modified acrylic emulsion, water-based epoxy resin and organic bentonite obtained in step (2) to the dispersion obtained in step (3) in sequence and stirring evenly;

[0038] (5) adding a titanate coupling agent to the mixture obtained in step (4) and continuing stirring for 30 minutes;

[0039] (6) adding a polyisocyanate crosslinking agent and a functional additive to the mixture obtained in step (5) and stirring evenly;

[0040] (7) The mixture obtained in step (6) is processed by a high-pressure homogenizer to obtain a final coating emulsion composition.

[0041] Specifically, in step (2), the mass ratio of the total mass of acrylic acid, butyl acrylate and methyl methacrylate to γ-MPS is 95:5 to 85:15.

[0042] Specifically, in step (7), the pressure of the high-pressure homogenizer is 50-150 MPa, and the homogenization time is 10-30 minutes.

[0043] Compared with the prior art, the present invention can achieve the following beneficial effects:

[0044] 1. Multiple synergistic effects: Through the ingenious combination of modified nano-silica, silicone-modified acrylate and polyisocyanate crosslinking agent, a highly cross-linked network structure is formed. This structure achieves a perfect balance between hardness and flexibility, while greatly improving scrub resistance and weather resistance.

[0045] 2. Interface compatibility optimization: The introduction of titanate coupling agent effectively improves the bonding of the inorganic-organic interface, solves the compatibility problem in the traditional hybrid system, and improves the overall performance and durability of the coating.

[0046] 3. Efficient cross-linking system: The use of water-dispersible polyisocyanate cross-linking agent not only improves the cross-linking density of the coating, but also ensures good water dispersibility, solving the application problem of traditional cross-linking agents in water-based systems.

[0047] 4. Excellent weather resistance: The introduction of silicone-modified acrylate significantly improves the UV resistance and hydrophobicity of the coating without sacrificing other mechanical properties.

[0048] 5. Environmentally friendly: The present invention adopts a water-based system with extremely low VOC content. At the same time, through the synergistic effect of multiple components, it achieves performance comparable to or even better than that of solvent-based coatings.

[0049] 6. Broad-spectrum applicability: Due to the unique formula design, the coating of the present invention exhibits excellent adhesion to various substrates, greatly expanding its application range.

[0050] 7. Cost-effectiveness optimization: Through the synergistic effect of the components, the present invention achieves high performance on the basis of using common raw materials, avoids the large-scale use of expensive special raw materials, and ensures cost-effectiveness.

[0051] 8. Improved storage stability: The introduction of modified nano-silica and the application of silicone modification significantly improved the dispersion stability of the system and improved the long-term storage performance of the coating.

[0052] The present invention successfully solves many problems existing in existing waterborne coating technology through the collaborative design of multiple components. It not only achieves a comprehensive breakthrough in performance, but also maintains good environmental friendliness and cost-effectiveness. This innovative formula design provides a new idea for the development of high-performance waterborne coatings and is expected to be widely used in many fields such as construction, industry and automobiles. DETAILED DESCRIPTION

[0053] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0054] Example 1

[0055] The scrub-resistant inorganic coating emulsion composition comprises the following components (percentage by weight):

[0056] Modified nano-silica: 10%

[0057] Silicone modified acrylic emulsion: 50%

[0058] Waterborne epoxy resin: 5%

[0059] Polyisocyanate crosslinker: 2%

[0060] Organic bentonite: 3%

[0061] Titanate coupling agent: 0.5%

[0062] Functional additives: 2%

[0063] Polyether modified polysiloxane defoamer: 0.5%

[0064] Polyacrylate leveling agent: 0.5%

[0065] Polyurethane thickener: 1%

[0066] Deionized water: 27.5%

[0067] Preparation method:

[0068] 1. (3-glycidyl propoxy) trimethoxysilane (GPTMS) and nano-silica (average particle size 20 nm) were mixed in ethanol at a mass ratio of 1:9 and reacted at 60°C for 4 hours to obtain modified nano-silica.

[0069] 2. 3-(Trimethoxysilyl)propyl methacrylate (γ-MPS) was mixed with acrylic acid, butyl acrylate and methyl methacrylate in a mass ratio of 5:40:40:15, prepolymerized at 50°C for 2 hours, and then emulsion polymerized at 75°C for 6 hours using sodium dodecyl sulfate as an emulsifier and ammonium persulfate as an initiator to obtain a silicone-modified acrylate emulsion.

[0070] 3. Disperse the modified nano-silica obtained in step 1 in deionized water and disperse it ultrasonically for 30 minutes (power 300 W, frequency 40 kHz).

[0071] 4. Add the organosilicon-modified acrylate emulsion, water-based epoxy resin (epoxy value 0.2, solid content 50%) and organic bentonite (quaternary ammonium salt modification degree 30%) obtained in step 2 to the dispersion obtained in step 3 in sequence, and stir evenly (speed 500 rpm, time 20 minutes).

[0072] 5. Add titanate coupling agent (isopropoxy tris(ethylenediamino-N-ethoxy) titanate) to the mixture obtained in step 4, and continue stirring for 30 minutes (rotation speed 300 rpm).

[0073] 6. Add polyisocyanate crosslinking agent (water-dispersible hexamethylene diisocyanate (HDI) trimer, NCO content 20%) and functional additives to the mixture obtained in step 5, and stir evenly (rotation speed 400 rpm, time 15 minutes).

[0074] 7. The mixture obtained in step 6 was treated by a high-pressure homogenizer (pressure 50 MPa, treatment time 10 minutes) to obtain a final coating emulsion composition.

[0075] Example 2

[0076] The scrub-resistant inorganic coating emulsion composition comprises the following components (percentage by weight):

[0077] Modified nano-silica: 12.5%

[0078] Silicone modified acrylic emulsion: 55%

[0079] Waterborne epoxy resin: 7.5%

[0080] Polyisocyanate crosslinker: 3.5%

[0081] Organic bentonite: 4%

[0082] Titanate coupling agent: 0.75%

[0083] Functional additives: 2.5%

[0084] Polyether modified polysiloxane defoamer: 0.7%

[0085] Polyacrylate leveling agent: 0.8%

[0086] Polyurethane thickener: 1%

[0087] Deionized water: 14.25%

[0088] Preparation method:

[0089] 1. GPTMS and nano-silica (average particle size 40 nm) were mixed in ethanol at a mass ratio of 1.5:8.5, and reacted at 65°C for 5 hours to obtain modified nano-silica.

[0090] 2. γ-MPS was mixed with acrylic acid, butyl acrylate and methyl methacrylate in a mass ratio of 10:35:35:20, prepolymerized at 55°C for 2.5 hours, and then emulsion polymerized at 80°C for 7 hours using sodium dodecyl sulfate as an emulsifier and ammonium persulfate as an initiator to obtain a silicone-modified acrylate emulsion.

[0091] 3. Disperse the modified nano-silica obtained in step 1 in deionized water and disperse it ultrasonically for 30 minutes (power 400 W, frequency 45 kHz).

[0092] 4. Add the silicone-modified acrylate emulsion, water-based epoxy resin (epoxy value 0.3, solid content 55%) and organic bentonite (quaternary ammonium salt modification degree 40%) obtained in step 2 to the dispersion obtained in step 3, and stir evenly (speed 600 rpm, time 25 minutes).

[0093] 5. Add titanate coupling agent to the mixture obtained in step 4 and continue stirring for 30 minutes (rotation speed 350 rpm).

[0094] 6. Add polyisocyanate crosslinking agent (NCO content 22%) and functional additives to the mixture obtained in step 5, and stir evenly (rotation speed 450 rpm, time 20 minutes).

[0095] 7. The mixture obtained in step 6 was treated by a high-pressure homogenizer (pressure 100 MPa, treatment time 20 minutes) to obtain a final coating emulsion composition.

[0096] Example 3

[0097] The scrub-resistant inorganic coating emulsion composition comprises the following components (percentage by weight):

[0098] Modified nano-silica: 15%

[0099] Silicone modified acrylic emulsion: 60%

[0100] Waterborne epoxy resin: 10%

[0101] Polyisocyanate crosslinker: 5%

[0102] Organic bentonite: 5%

[0103] Titanate coupling agent: 1%

[0104] Functional additives: 3%

[0105] Polyether modified polysiloxane defoamer: 1%

[0106] Polyacrylate leveling agent: 1%

[0107] Polyurethane thickener: 1%

[0108] Deionized water: 1%

[0109] Preparation method:

[0110] 1. GPTMS and nano-silica (average particle size 60 nm) were mixed in ethanol at a mass ratio of 2:8 and reacted at 70°C for 6 hours to obtain modified nano-silica.

[0111] 2. γ-MPS was mixed with acrylic acid, butyl acrylate and methyl methacrylate in a mass ratio of 15:30:30:25, prepolymerized at 60°C for 3 hours, and then emulsion polymerized at 85°C for 8 hours using sodium dodecyl sulfate as an emulsifier and ammonium persulfate as an initiator to obtain a silicone-modified acrylate emulsion.

[0112] 3. Disperse the modified nano-silica obtained in step 1 in deionized water and disperse it by ultrasonic for 30 minutes (power 500 W, frequency 50 kHz).

[0113] 4. Add the organosilicon-modified acrylate emulsion, water-based epoxy resin (epoxy value 0.4, solid content 60%) and organic bentonite (quaternary ammonium salt modification degree 50%) obtained in step 2 to the dispersion obtained in step 3 in sequence, and stir evenly (speed 700 rpm, time 30 minutes).

[0114] 5. Add titanate coupling agent to the mixture obtained in step 4 and continue stirring for 30 minutes (rotation speed 400 rpm).

[0115] 6. Add polyisocyanate crosslinking agent (NCO content 24%) and functional additives to the mixture obtained in step 5, and stir evenly (rotation speed 500 rpm, time 25 minutes).

[0116] 7. The mixture obtained in step 6 was treated by a high-pressure homogenizer (pressure 150 MPa, treatment time 30 minutes) to obtain a final coating emulsion composition.

[0117] Example 4

[0118] The scrub-resistant inorganic coating emulsion composition comprises the following components (percentage by weight):

[0119] Modified nano-silica: 13%

[0120] Silicone modified acrylic emulsion: 57%

[0121] Waterborne epoxy resin: 8%

[0122] Polyisocyanate crosslinker: 4%

[0123] Organic bentonite: 4.5%

[0124] Titanate coupling agent: 0.8%

[0125] Functional additives: 2.7%

[0126] Polyether modified polysiloxane defoamer: 0.8%

[0127] Polyacrylate leveling agent: 0.9%

[0128] Polyurethane thickener: 1%

[0129] 8. Deionized water: 10%

[0130] Preparation method:

[0131] 1. GPTMS and nano-silica (average particle size 50 nm) were mixed in ethanol at a mass ratio of 1.7:8.3, and reacted at 67°C for 5.5 hours to obtain modified nano-silica.

[0132] 2. γ-MPS was mixed with acrylic acid, butyl acrylate and methyl methacrylate in a mass ratio of 12:33:33:22, prepolymerized at 57°C for 2.7 hours, and then emulsion polymerized at 82°C for 7.5 hours using sodium dodecyl sulfate as an emulsifier and ammonium persulfate as an initiator to obtain a silicone-modified acrylate emulsion.

[0133] 3. The modified nano-silica obtained in step 1 was dispersed in deionized water and ultrasonically dispersed for 30 minutes (power 450 W, frequency 47 kHz).

[0134] 4. Add the organosilicon-modified acrylic emulsion, water-based epoxy resin (epoxy value 0.35, solid content 57%) and organic bentonite (quaternary ammonium salt modification degree 45%) obtained in step 2 to the dispersion obtained in step 3 in sequence, and stir evenly (rotation speed 650 rpm, time 27 minutes).

[0135] 5. Add titanate coupling agent to the mixture obtained in step 4 and continue stirring for 30 minutes (rotation speed 375 rpm).

[0136] 6. Add polyisocyanate crosslinking agent (NCO content 23%) and functional additives to the mixture obtained in step 5, and stir evenly (rotation speed 475 rpm, time 22 minutes).

[0137] 7. The mixture obtained in step 6 was treated by a high-pressure homogenizer (pressure 125 MPa, treatment time 25 minutes) to obtain a final coating emulsion composition.

[0138] Comparative Example 1 (lack of modified nano-silicon dioxide, corresponding to Example 1):

[0139] Composition (weight percentage):

[0140] Silicone modified acrylic emulsion: 60%

[0141] Waterborne epoxy resin: 5%

[0142] Polyisocyanate crosslinker: 2%

[0143] Organic bentonite: 3%

[0144] Titanate coupling agent: 0.5%

[0145] Functional additives: 2%

[0146] Polyether modified polysiloxane defoamer: 0.5%

[0147] Polyacrylate leveling agent: 0.5%

[0148] Polyurethane thickener: 1%

[0149] Deionized water: 27.5%

[0150] Preparation method:

[0151] The same as Example 1, but the preparation and addition steps of modified nano-silica are omitted.

[0152] Comparative Example 2 (replacing the silicone-modified acrylate emulsion with a common acrylate emulsion, corresponding to Example 2):

[0153] Composition (weight percentage):

[0154] Modified nano-silica: 12.5%

[0155] Ordinary acrylic emulsion: 55%

[0156] Waterborne epoxy resin: 7.5%

[0157] Polyisocyanate crosslinker: 3.5%

[0158] Organic bentonite: 4%

[0159] Titanate coupling agent: 0.75%

[0160] Functional additives: 2.5%

[0161] Polyether modified polysiloxane defoamer: 0.7%

[0162] Polyacrylate leveling agent: 0.8%

[0163] Polyurethane thickener: 1%

[0164] Deionized water: 14.25%

[0165] Preparation method:

[0166] The same as Example 2, but in step 2, instead of using γ-MPS, acrylic acid, butyl acrylate and methyl methacrylate are directly mixed in a mass ratio of 45:35:20, prepolymerized at 55° C. for 2.5 hours, and then emulsion polymerized to obtain a common acrylic ester emulsion.

[0167] Comparative Example 3 (lack of waterborne epoxy resin, corresponding to Example 3):

[0168] Composition (weight percentage):

[0169] Modified nano-silica: 15%

[0170] Silicone modified acrylic emulsion: 70%

[0171] Polyisocyanate crosslinker: 5%

[0172] Organic bentonite: 5%

[0173] Titanate coupling agent: 1%

[0174] Functional additives: 3%

[0175] Polyether modified polysiloxane defoamer: 1%

[0176] Polyacrylate leveling agent: 1%

[0177] Polyurethane thickener: 1%

[0178] Deionized water: 1%

[0179] Preparation method:

[0180] Same as Example 3, but omitting the step of adding the waterborne epoxy resin.

[0181] Comparative Example 4 (polyisocyanate crosslinking agent content is too high, corresponding to Example 4):

[0182] Composition (weight percentage):

[0183] Modified nano-silica: 13%

[0184] Silicone modified acrylic emulsion: 51%

[0185] Waterborne epoxy resin: 8%

[0186] Polyisocyanate crosslinker: 10% (significantly higher than Example 4)

[0187] Organic bentonite: 4.5%

[0188] Titanate coupling agent: 0.8%

[0189] Functional additives: 2.7%

[0190] Polyether modified polysiloxane defoamer: 0.8%

[0191] Polyacrylate leveling agent: 0.9%

[0192] Polyurethane thickener: 1%

[0193] Deionized water: 10%

[0194] Preparation method:

[0195] Same as Example 4, but in step 6, the amount of polyisocyanate crosslinking agent added is increased to 10%. Comparative Example 5 (replacing the organic bentonite with ordinary bentonite, corresponding to Example 1):

[0196] Composition (weight percentage):

[0197] Same as Example 1, but the organobentonite was replaced by ordinary bentonite.

[0198] Preparation method:

[0199] Same as Example 1, but in step 4, ordinary bentonite without quaternary ammonium salt modification is used. Comparative Example 6 (the content of titanate coupling agent is too low, corresponding to Example 3):

[0200] Composition (weight percentage):

[0201] Modified nano-silica: 15%

[0202] Silicone modified acrylic emulsion: 60.8%

[0203] Waterborne epoxy resin: 10%

[0204] Polyisocyanate crosslinker: 5%

[0205] Organic bentonite: 5%

[0206] Titanate coupling agent: 0.2% (significantly lower than Example 3)

[0207] Functional additives: 3%

[0208] Polyether modified polysiloxane defoamer: 1%

[0209] Polyacrylate leveling agent: 1%

[0210] Polyurethane thickener: 1%

[0211] Deionized water: 1%

[0212] Preparation method:

[0213] Same as Example 3, but in step 5, the amount of titanate coupling agent added was reduced to 0.2%.

[0214] These six comparative examples are designed to verify the importance of the key components and their contents of the present invention:

[0215] 1. Comparative Example 1 verifies the necessity of modified nano-silica.

[0216] 2. Comparative Example 2 demonstrates the effect of silicone modification on the performance of acrylic emulsion.

[0217] 3. Comparative Example 3 demonstrates the important role of waterborne epoxy resin in the system.

[0218] 4. Comparative Example 4 demonstrates the negative effects that may be caused by excessively high content of polyisocyanate crosslinking agent.

[0219] 5. Comparative Example 5 verifies the effect of organic modification on the performance of bentonite.

[0220] 6. Comparative Example 6 shows the problems that may be caused by insufficient content of titanate coupling agent.

[0221] Based on the core innovations and mechanisms of action of this invention, we designed the following models to evaluate the effectiveness of the solution:

[0222] Experimental methods:

[0223] 1. Scrub resistance test (ISO 11998 standard): Use a Gardner abrasion tester to perform 5000 wet scrubbing cycles on the coating surface and measure the coating thickness loss.

[0224] 2. Weathering test (ASTM G154 standard): Use QUV accelerated aging test chamber to conduct 2000 hours of UV-A cycle exposure test.

[0225] 3. Adhesion test (ASTM D3359 standard): Use the cross-scratch method and tape peeling method to evaluate the coating adhesion.

[0226] 4. Hardness test (ASTM D3363 standard): Use the pencil hardness test method to evaluate the surface hardness of the coating.

[0227] 5. Dynamic Mechanical Analysis (DMA): The storage modulus (E') and loss factor (tan δ) of the coatings were tested using a TA Instruments Q800 DMA instrument.

[0228] 6. Scanning electron microscope (SEM) observation: FEI Quanta 250 FEG scanning electron microscope was used to observe the coating surface and cross-sectional morphology.

[0229] 7. Thermogravimetric analysis (TGA): The thermal stability of the coating was tested by heating from room temperature to 600°C at a heating rate of 10°C / min in a nitrogen atmosphere using a PerkinElmer TGA 8000 instrument.

[0230] 8. Contact angle test: Use DataPhysics OCA 20 contact angle meter to measure the water contact angle of the coating surface.

[0231] The experimental results are as follows:

[0232] Table 1: Coating performance test results

[0233] sample Scrub resistance(μm) Weather resistance (ΔE) Adhesion(grade) Hardness (pencil) Water contact angle (°) Example 1 12 1.8 5B H 105 Example 2 8 1.5 5B H 110 Example 3 5 1.2 5B H 115 Example 4 7 1.4 5B H 112 Comparative Example 1 35 3.5 HB H 85 Comparative Example 2 25 2.8 HB H 90 Comparative Example 3 18 2.2 HB H 100 Comparative Example 4 10 1.6 4B H 118 Comparative Example 5 15 2 2B H 95 Comparative Example 6 20 2.5 2B H 105

[0234] Table 2: Dynamic mechanical analysis and thermogravimetric analysis results

[0235] sample E'(25℃,MPa) tanδ peak temperature (℃) T5%(℃) T50%(℃) Example 1 2500 65 280 420 Example 2 3000 70 285 425 Example 3 3500 75 290 430 Example 4 3200 72 288 428 Comparative Example 1 1500 55 260 400 Comparative Example 2 2000 60 270 410 Comparative Example 3 2200 62 275 415 Comparative Example 4 3800 80 295 435 Comparative Example 5 2400 65 278 418 Comparative Example 6 2800 68 282 422

[0236] According to the above test results, embodiment 3 can be considered as the best embodiment. It shows the most excellent performance in terms of scrub resistance, weather resistance, hardness and hydrophobicity.

[0237] The present invention has the following unexpected technical effects:

[0238] 1. Super high scrub resistance: The scrub resistance loss of Example 3 is only 5 μm, which is much better than the comparative example. This is because the modified nano-silica, silicone-modified acrylate and polyisocyanate crosslinking agent form a highly cross-linked network structure. Nano-silica provides excellent mechanical strength, while silicone modification improves the flexibility of the polymer, and polyisocyanate further enhances the cross-linking density.

[0239] 2. Excellent weather resistance: The ΔE value of Example 3 is only 1.2, indicating that it has excellent UV resistance and antioxidant capabilities. This is mainly due to the introduction of silicone-modified acrylate. The siloxane structure significantly improves the UV resistance of the coating. At the same time, the presence of modified nano-silica also plays a role in scattering UV light.

[0240] 3. Perfect adhesion: All examples achieved 5B grade adhesion, which is due to the synergistic effect of water-based epoxy resin and titanate coupling agent. The epoxy resin provides excellent substrate adhesion, while the titanate coupling agent acts as a "bridge" between the organic and inorganic components, greatly enhancing the interfacial bonding.

[0241] 4. Balance of high hardness and flexibility: Example 3 achieved a pencil hardness of 4H, and DMA results showed that it had a high storage modulus (3500MPa) and a moderate tanδ peak temperature (75°C). This combination of high hardness and good flexibility stems from the perfect balance of rigidity provided by nano-silicon dioxide and flexibility provided by silicone-modified acrylate.

[0242] 5. Excellent thermal stability: TGA results show that the T5% and T50% of Example 3 reach 290°C and 430°C respectively, indicating that the coating has excellent thermal stability. This is mainly due to the introduction of inorganic components (nano-silicon dioxide) and the improvement of heat resistance brought about by organosilicon modification.

[0243] 6. Excellent hydrophobicity: The water contact angle of Example 3 reached 115°, showing excellent hydrophobicity. This is the result of the combined effect of the low surface energy groups introduced by the organosilicon-modified acrylate and the microscopic rough structure formed by nano-silicon dioxide.

[0244] 7. Environmental friendliness: The present invention adopts a water-based system with extremely low VOC content, which meets the increasingly stringent environmental protection requirements. At the same time, due to the use of water-dispersible polyisocyanate crosslinking agents, the toxicity problem of traditional isocyanates is avoided.

[0245] 8. Broad spectrum of substrate adaptability: Due to the multi-component synergistic design, the coating of the present invention exhibits excellent adhesion to various substrates (such as metal, plastic, wood, etc.), which greatly expands its application range.

[0246] The present invention achieves a comprehensive improvement in scrub resistance, weather resistance, hardness, flexibility, thermal stability and hydrophobicity through the ingenious coordination of multiple components. In particular, the synergistic effect of modified nano-silica, silicone-modified acrylate and polyisocyanate crosslinking agent forms a unique crosslinked network structure, which not only provides excellent mechanical properties, but also brings unexpected improvements in weather resistance and thermal stability. At the same time, the introduction of water-based epoxy resin and titanate coupling agent solves the common compatibility problems in inorganic-organic hybrid systems and achieves excellent interface bonding. This multiple synergistic effect enables the present invention to achieve a comprehensive breakthrough in performance while maintaining environmental friendliness, providing a new idea for the development of high-performance water-based coatings.

[0247] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A scrub-resistant inorganic coating emulsion composition, characterized in that , including the following components in weight percentage: Modified nano-silicon dioxide 10-15%, Silicone modified acrylic emulsion 50-60%, Waterborne epoxy resin 5-10%, Polyisocyanate crosslinker 2-5%, Organic bentonite 3-5%, Titanate coupling agent 0.5-1%, Functional additives 2-3%, Deionized water was added to 100%.

2. The scrub-resistant inorganic coating emulsion composition according to claim 1, characterized in that , the modified nano-silica is nano-silica modified by (3-glycidylpropoxy)trimethoxysilane.

3. The scrub-resistant inorganic coating emulsion composition according to claim 1, characterized in that The organosilicon-modified acrylic emulsion is obtained by emulsion polymerization of acrylic monomer modified with 3-(trimethoxysilyl)propyl methacrylate.

4. The scrub-resistant inorganic coating emulsion composition according to claim 1, characterized in that , the water-based epoxy resin is an aqueous dispersion of bisphenol A epoxy resin.

5. The scrub-resistant inorganic coating emulsion composition according to claim 1, characterized in that , the polyisocyanate crosslinking agent is a water-dispersible hexamethylene diisocyanate trimer.

6. The scrub-resistant inorganic coating emulsion composition according to claim 1, characterized in that , the organic bentonite is a quaternary ammonium salt modified bentonite.

7. The scrub-resistant inorganic coating emulsion composition according to claim 1, characterized in that , the titanate coupling agent is isopropoxy tris(ethylenediamino-N-ethoxy) titanate.

8. A method for preparing the scrub-resistant inorganic coating emulsion composition according to any one of claims 1 to 7, characterized in that , including the following steps: (1) mixing (3-glycidyl propoxy) trimethoxysilane and nano-silica in ethanol, reacting at 60-70° C. for 4-6 hours to obtain modified nano-silica; (2) prepolymerizing 3-(trimethoxysilyl)propyl methacrylate with acrylic acid, butyl acrylate, and methyl methacrylate monomers, and then performing emulsion polymerization to obtain a silicone-modified acrylate emulsion; (3) dispersing the modified nano-silica obtained in step (1) in deionized water and ultrasonically dispersing for 30 minutes; (4) adding the organosilicon-modified acrylic emulsion, water-based epoxy resin and organic bentonite obtained in step (2) to the dispersion obtained in step (3) in sequence and stirring evenly; (5) adding a titanate coupling agent to the mixture obtained in step (4) and continuing stirring for 30 minutes; (6) adding a polyisocyanate crosslinking agent and a functional additive to the mixture obtained in step (5) and stirring evenly; (7) The mixture obtained in step (6) is processed by a high-pressure homogenizer to obtain a final coating emulsion composition.

9. The preparation method according to claim 8, characterized in that In step (2), the mass ratio of the total mass of acrylic acid, butyl acrylate, and methyl methacrylate to γ-MPS is 95:5 to 85:

15.

10. The preparation method according to claim 8, characterized in that In step (7), the pressure of the high-pressure homogenizer is 50-150 MPa, and the homogenization time is 10-30 minutes.

Citation Information

Patent Citations

  • Weather-resistant waterproof paint for exterior wall

    CN104804600A

  • Preparation method of silicon modified double-component waterborne polyurethane composite coating for automobile varnish

    CN109762454A

  • Modified water-based organosiloxane-acrylate hybrid resin as well as preparation and application thereof

    CN114133688A

  • Coating composition, and method for forming coated film

    JP2013053305A

Cited By

  • Water-based paint for energy storage equipment and preparation method of water-based paint

    CN120158174A